1996
DOI: 10.1001/archsurg.1996.01430210084018
|View full text |Cite
|
Sign up to set email alerts
|

No Difference in Catheter Sepsis Between Standard and Antiseptic Central Venous Catheters

Abstract: In this study, there were no statistically significant differences in the incidence of catheter-related sepsis or catheter site infections between the standard and antiseptic groups. Future prospective, randomized controlled trials with a larger number of antiseptic catheters are encouraged to confirm or refute these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 6 publications
1
68
1
Order By: Relevance
“…However, even if these cases of CRB are excluded, the differences in the rates of bacteremia remain insignificant. These findings are in agreement with 2 recent studies 17,18 evaluating the efficacy of CVCs coated with CSS in patients receiving total parenteral nutrition.…”
Section: 33-35supporting
confidence: 92%
“…However, even if these cases of CRB are excluded, the differences in the rates of bacteremia remain insignificant. These findings are in agreement with 2 recent studies 17,18 evaluating the efficacy of CVCs coated with CSS in patients receiving total parenteral nutrition.…”
Section: 33-35supporting
confidence: 92%
“…Other studies that have demonstrated a reduced rate of skin colonization and bacteremias include those involving catheters coated with chorhexidine-silver sulfadiazine (21,22,42,43) or minocycline and rifampin (20). These studies are limited by their short-term catheterization and efficacy (42), reduced antimicrobial activity over time (43,44), potential for microbial resistance (45), and generalizability to the chronic hemodialysis population.…”
Section: Discussionmentioning
confidence: 99%
“…Authors were contacted for these nine studies; no more information was available for three, 11,54,60 no reply was received from four 53,61,65,72 and two authors said that they did not investigate either CRBSI or colonisation.…”
Section: Bias-funnel Plotsmentioning
confidence: 99%